Halo Data Understanding and Leveraging the Value of your Data - Carruthers, Caroline ca. 20./21. Jh; Jackson, Peter 1962- (Facet Publishing, 2023)
This book helps readers understand what data can do, how to unlock value from your data and how you use it to change the game in your organisation